2009
DOI: 10.1002/hec.1478
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental health insurance and equality of access in Belgium

Abstract: The effects of supplemental health insurance on health-care consumption crucially depend on specific institutional features of the health-care system. We analyse the situation in Belgium, a country with a very broad coverage in compulsory social health insurance and where supplemental insurance mainly refers to extra-billing in hospitals. Within this institutional background, we find only weak evidence of adverse selection in the coverage of supplemental health insurance. We find much stronger effects of socio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…Cline, Mott study of demand for supplementary drug plans in elderly Medicare members showed that increased elderly drug expenditures over the previous 30 months and increased drug used by them in this period increased their likelihood of membership in supplementary drug plans ( Cline & Mott, 2003 ). The positive effect of medical expenses on increasing demand for medical insurance is in line with previous studies ( Alegria et al, 2006 ; Schokkaert, Van Ourti, De Graeve, Lecluyse & Van de Voorde, 2010 ; Yellaiah & Ramakrishna, 2012 ).…”
Section: Discussionsupporting
confidence: 90%
“…Cline, Mott study of demand for supplementary drug plans in elderly Medicare members showed that increased elderly drug expenditures over the previous 30 months and increased drug used by them in this period increased their likelihood of membership in supplementary drug plans ( Cline & Mott, 2003 ). The positive effect of medical expenses on increasing demand for medical insurance is in line with previous studies ( Alegria et al, 2006 ; Schokkaert, Van Ourti, De Graeve, Lecluyse & Van de Voorde, 2010 ; Yellaiah & Ramakrishna, 2012 ).…”
Section: Discussionsupporting
confidence: 90%
“…There is significant evidence that the decision to purchase a VPHI policy is mostly determined by socio-economic variables such as income, wealth, education, social class and employment status (e.g. Cameron et al, 1988;Wolfe and Goddeeris, 1991;Hurd and McGarry, 1997;Vera-Hernandez, 1999;van Doorslaer et al, 2004;Jones et al, 2006;Dormont et al, 2007;Doiron et al, 2008;Dardanoni and Li Donni, 2009;Schokkaert et al, 2010;Bolin et al, 2010) and by cognitive ability (Fang et al, 2008), whereas a clear relationship between observable health measures and the probability to hold or purchase private supplemental insurance is not found, probably because the empirical literature does not provide consistent evidence of the role of adverse selection and because of cream skimming by private insurers. Recently, Bolin et al (2010) revisit these arguments and observe a negative correlation between risk (measured by selfassessed health) and insurance but find no evidence of heterogeneous risk preferences as an explanation of this finding.…”
Section: Review Of Literaturementioning
confidence: 99%
“…In France, more than 80% of insured households are covered for the reimbursement of co-payments (for outpatient and inpatient care, and for drugs), of dental care and of optical prostheses, confirming that VPHI predominantly complements public coverage. In Belgium, VPHI mostly covers full costs of hospital care (75.6% of insured households) and an extended choice of hospitals (40% of insured households), and therefore, it seems predominantly supplementary of public coverage (Schokkaert et al, 2010).…”
Section: Datamentioning
confidence: 99%
“…At the system-level there are also differences between different types of voluntary private insurance. We can distinguish between three main types: duplicate, supplementary, and complementary coverage [ 21 – 23 ]. The duplicate system covers services already included in the mandatory health insurance.…”
Section: Methodsmentioning
confidence: 99%